Leadership of multicultural teams at a french company: project globe based study - Costa, Mafalda Marques Ferreira da (2018)
Leadership is always present in everyone’s professional life, challenging managers and leaders, especially when they need to manage teams. Nevertheless, the challenge is even bigger when they have to manage a team composed by people with different cultural backgrounds. This dissertation falls under the leadership scope and its aim is to characterise the leadership style of multicultural teams at a French company operating in Portugal for more than 30 years, using a deductive study case. This study is based in the project GLOBE’s theory (Global Leadership and Organisational Behaviour Effectiveness), an investigation initiated in the 90’s by Robert House, which objective is to investigate the relationship between culture and organisational behaviour. By taking advantage of the questionnaire already created by GLOBE, the employees of this French organisation were asked to rate 89 leadership attributes using a 7-point scale, where 1 stands for a characteristic that greatly inhibits a person from being an outstanding leader and 7 stands for a characteristic that greatly contributes to a person being an outstanding leader. The results obtained in this questionnaire enabled to determine the leadership attributes more desirable by the employees and to verify that charismatic/value-based leadership style is the most preferable one. In addition, this investigation shows that both managers and subordinates value the same leadership features, which suggests that the leadership in this company is effective. At the end of this dissertation, the main conclusions, limitations and future research suggestions are presented.